Survey Attitude Toward The Level Of Understanding Of Descriptive Statistics by Students in Higher Education: Pair Comparison Methode - Nusrotus Sa’idah; Jailani; Sudiyatno (LPPM Undiksha, 2024)
Many people find statistics very difficult. This impacts students not only on their academic performance but also on unpleasant influences or negative perceptions. This research aims to produce a scaling instrument for attitudes toward student statistics levels using the pair comparison method with valid and reliable characteristics. This research is a quantitative descriptive research by developing a research instrument with a pair comparison scale. The subjects of this research were 160 students who had received courses. This instrument consists of 11 dimensions that measure students' attitudes toward their level of understanding of statistics. The analysis uses quantitative description. The results of scaling the student attitude instrument towards the level of understanding of statistics using the pair comparison method show that the characteristics of each dimension are valid and the Cronbach value meets high-reliability criteria. The results of scaling the attitude instrument towards statistical material with the highest average response order were in the material understanding mode,